2006
DOI: 10.1016/j.ydbio.2006.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Olig2 transcription factor in cholinergic neuron development of the basal forebrain

Abstract: Cholinergic neurons, which express choline acetyltransferase (ChAT), are a major neuron subset generated in the basal forebrain. Areas presumed to be sites of origin of cholinergic neurons are roughly demarcated by expression of Olig2, a basic helix-loop-helix transcription factor, which includes the medial ganglionic eminence, septal area, and anterior entopeduncular/preoptic area. In the present study, we examined the involvement of Olig2 in cholinergic differentiation. When the Olig2-expressing cells at E12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…Olig2 is a bHLH transcriptional repressor protein that plays essential roles in the lineage specification of progenitor cells into neuronal subtypes (somatic motor neurons and forebrain cholinergic neurons) and oligodendrocytes during central nervous system development [60][61][62][63][64][65][66]. At early embryonic stages, one key role of Olig2 is to maintain progenitor cells in a replication-competent state [67].…”
Section: Discussionmentioning
confidence: 99%
“…Olig2 is a bHLH transcriptional repressor protein that plays essential roles in the lineage specification of progenitor cells into neuronal subtypes (somatic motor neurons and forebrain cholinergic neurons) and oligodendrocytes during central nervous system development [60][61][62][63][64][65][66]. At early embryonic stages, one key role of Olig2 is to maintain progenitor cells in a replication-competent state [67].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the colocalization of oligodendrocyte transcription factor 2 (Olig.2), a marker specific for OPC (Furusho et al 2006), and HIF1α was evaluated by immunostaining. The coronal sections were fixed with 4% paraformaldehyde (Wako Pure Chemical Industries, Ltd, Osaka, Japan) for 30 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Forebrain cholinergic neurons arise early in telencephalic development (~E10 in mouse which approximately corresponds to gestational day 40 in humans; Clancy et al, 2001) in the medial ganglionic eminence, a ventricular/subventricular neurogenic zone that appears as a thickening along the ventral/medial wall of the ventricle (Brady et al, 1989;Furusho, 2006;Marin et al, 2000;Olsson et al, 1998;Semba et al, 1988). Presumptive forebrain projection cholinergic neurons migrate from the MGE (and possibly from the anterior entopeduncular/preoptic area) radially to take up locations in basal forebrain nuclei (medial septum, magnocellular nucleus, diagonal band of Broca), whereas the striatal cholinergic interneurons migrate tangentially from the MGE, occupying dispersed sites throughout the striatal plate.…”
Section: A Development Of Cholinergic Systemsmentioning
confidence: 99%
“…In particular, the basics of a cholinergic transcription factor code are emerging. A variety of experimental approaches has demonstrated that expression of several transcription factors is important (Mash 1, Olig2, Lmx7, Lmx8) or essential (Nkx2.1) for generating forebrain cholinergic neurons (Bachy and Retaux, 2006;Furusho et al, 2006;Marin et al, 2000;Mori et al, 2004;Zhao et al, 2003). Thus, the combined expression of these factors, and their target genes, probably accounts for much of the intrinsic identity of the cholinergic phenotype.…”
Section: A Development Of Cholinergic Systemsmentioning
confidence: 99%